Pengaruh Supervisi Akademik Berbasis AVOS dan Tindak Lanjut Pasca Supervisi terhadap Kualitas Pembelajaran - Simbolon, Ali Mustopa Yakub; Zakir, Supratman (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
The quality of education at MTI Canduang faces several challenges, with 40 out of 92 teachers not fully aligned in terms of their educational qualifications and the subjects they teach. Additionally, 60% of teachers demonstrate effective teaching skills, 40% exhibit high motivation in the learning process, such as engaging in interactive discussions and providing constructive feedback, and 36% actively utilize technology in teaching, including digital presentations and instructional videos. This study aims to analyze the influence of AVOS-based Academic Supervision and Post-Supervision Follow-Up on the Quality of Education in Islamic Boarding Schools across Agam Regency. The research employs a quantitative approach with a correlational design, using questionnaires as the primary data collection instrument. The findings reveal: 1) AVOS-based Academic Supervision has a correlation with the Quality of Education (r = 0.542, p = 0.000). 2) Post-Supervision Follow-Up significantly affects the Quality of Education (r = 0.595, p = 0.000). 3) AVOS-based Academic Supervision and Post-Supervision Follow-Up collectively influence the Quality of Education. Simultaneous ANOVA testing indicates that F calculated (24.399) > F table (3.10) with a significance level of 0.000 < 0.05. These results underscore the critical role of supervision and follow-up actions in enhancing educational quality.